Penerapan Kegiatan Belajar Dari Rumah (BDR) Di Taman Kanak Kanak Annur Labuange - Rahmi, Andi Nur; Bachtiar, Muhammad Yusri; Syamsuardi, Syamsuardi (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2024)
This study examines Learning From Home (BDR) during the pandemic. The purpose of this study is the application of learning from home (BDR) activities in Annur Labuange Kindergarten, Knowing the supporting factors in implementing learning from home activities (BDR) in kindergarten Annur Labuange, knowing the inhibiting factors in the implementation of learning from home (BDR) activities in Annur Labuange Kindergarten. The approach used in this study is a qualitative approach with a descriptive type of research. The sample used in this study collected 12 people. The data collection techniques used were observation, interviews, documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing. The results of this study indicate that the method used by schools to carry out learning is blended learning or combining offline and online learning with several inhibiting and supporting factors. The implementation of learning is starting by preparing lesson plans, implementing bold learning through communication media such as WhatsAPP, Zoom. offline assistance from parents/guardians according to the schedule and assignments that have been made, each student working on the assignments that are distributed every week and the results of the following assignments monitor daily activities carried out every week on assignments and assignments for the following week.